Pengembangan modul ajar pada implementasi kurikulum merdeka untuk meningkatkan mutu proses pembelajaran dan hasil belajar peserta didik - Evy Fitria Islamiati; I Wayan Subagia; Ketut Suma (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to describe and explain the characteristics, validity, practicality, and effectiveness of teaching modules in the implementation of the independent curriculum to improve the quality of the learning process and student learning outcomes. This type of research is development research to produce learning tools in the form of science project teaching modules for SMK that are valid, practical, and effective. The development model used is a 4D adaptation model, which is composed of the stages of defining, designing, developing, and disseminating. Data collection was carried out using questionnaires and test techniques. The research results show that the teaching module used had characteristics with a table format arranged based on modifications from the Ministry of Education and Culture. The teaching module was in accordance with the multimedia and computer and network engineering departments. The results of the validity test show that the summarized teaching module was classified as very valid in terms of the validity of the content, material, and language. Based on teacher assessment, the teaching module was classified as very practical. The results of the effectiveness test show that the teaching module was effective in improving the quality of the learning process and student learning outcomes.